Sports genetics: the PPARA gene and athletes’ high ability in endurance sports. A systematic review and meta-analysis - Lopez-Leon, S; Tuvblad, C; Forero, DA (Biology of Sport, 2016)
A meta-analysis was performed with the aim of re-evaluating the role of the peroxisome proliferator activated receptor alpha ( PPARA ) gene intron 7 G/C polymorphism (rs4253778) in athletes‘ high ability in endurance sports. Design: A meta-analysis of case control studies assessing the association between the G/C polymorphisms of the PPARA gene and endurance sports was conducted. The Cochrane Review Manager software was used to compare the genotype and allele frequencies between endurance athletes and controls to determine whether a genetic variant is more common in athletes than in the general population. Five studies, encompassing 760 endurance athletes and 1792 controls, fulfilled our inclusion criteria. The pooled odds ratio (and confidence intervals, Cls) for the G allele compared to the C allele was 1.65 (95% Cl 1.39-1.96). The pooled OR for the GG genotype compared to the GC genotype was 1.79 (95% Cl 1.44-2.22), and for the GG genotype compared to the CC genotype 2.37 (95% Cl 1.40-3.99). There was no evidence of heterogeneity (I1 =0“/n) or of publication bias. Athletes with high ability in endurance sports had a higher frequency of the GG genotype and G allele.